The Ketamine Analogue Methoxetamine and 3- and 4-Methoxy Analogues of Phencyclidine Are High Affinity and Selective Ligands for the Glutamate NMDA Receptor - Roth, Bryan L.; Gibbons, Simon; Arunotayanun, Warunya; Huang, Xi-Ping; Setola, Vincent; Treble, Ric; Iversen, Les (PLOS ONE, 2013)
In this paper we determined the pharmacological profiles of novel ketamine and phencyclidine analogues currently used as ‘designer drugs’ and compared them to the parent substances via the resources of the National Institute of Mental Health Psychoactive Drug Screening Program. The ketamine analogues methoxetamine ((RS)-2-(ethylamino)-2-(3-methoxyphenyl)cyclohexanone) and 3-MeO-PCE (N-ethyl-1-(3-methoxyphenyl)cyclohexanamine) and the 3- and 4-methoxy analogues of phencyclidine, (1-[1-(3-methoxyphenyl)cyclohexyl]piperidine and 1-[1-(4-methoxyphenyl)cyclohexyl]piperidine), were all high affinity ligands for the PCP-site on the glutamate NMDA receptor. In addition methoxetamine and PCP and its analogues displayed appreciable affinities for the serotonin transporter, whilst the PCP analogues exhibited high affinities for sigma receptors. Antagonism of the NMDA receptor is thought to be the key pharmacological feature underlying the actions of dissociative anaesthetics. The novel ketamine and PCP analogues had significant affinities for the NMDA receptor in radioligand binding assays, which may explain their psychotomimetic effects in human users. Additional actions on other targets could be important for delineating side-effects.